Availability and Accessibility of Web-OPAC of University Libraries in Nigeria - Fabunmi Oluwatobi, M.; Olufemi, Asubiojo Bukky (Journal of Information and Knowledge, 2015)
This research explored the availability and accessibility of web-based OPAC in Nigerian university libraries. An Internet survey checklist targeted at all the 124 university libraries in Nigeria was developed and used. Libraries that could not be located on the Internet were excluded from the study which leaves 64 university libraries to be used for the study. The study revealed that 48.5% of Nigerian university libraries could not be located on the Internet because there was no link to them on their university websites. Finding further indicated that 25.3% were not directly hyperlinked on their university websites. The result also showed that only 29.7% of the Nigerian university libraries have website, while only 10.9% provided web-based OPAC to distant and remote users. Result also shows that only 9.4% of the available web-based OPAC were accessible. Hence, the study concluded that the majority of university libraries in Nigeria were lacking behind in the provision of flexible services which focus on individualized and distant contacts with their clientele. Therefore, the study recommended direct hyperlink to the university libraries on their parent institution websites; development of websites through which the libraries can disseminate information about their resources and services to information seekers on the Internet and suggested provision of web-based OPAC to be one of the criteria for assessing a university library services by the National University Commission.